Report for the year 1943-44 - Layton, Eleanor Dorothea, Lady
1944-03-14 035-0082-004 REPORT FOR THE YEAR 1943-44 The National Joint Committee for Spanish Relief and Basque Children's Trust completes its seventh year of work for the Basque children and Spaniards under its care who still remain in this country—411 of the children (254 boys and 157 girls) remain in the care of the Committee out of the 4,000 children taken charge of during those grave days of May, 1937. During the last year the activities of the National Joint Committee for Spanish Relief have been many and varied, and despite the new difficulties which the war has brought, the Committee has been able to continue its responsibilities. As we reported in 1942, the position for the adult Spaniard has improved, as all under our care, but one invalid, are now employed. Work for them goes on, and although the scope and direction of activities are limited by the necessities of war, the aim remains to see that men get jobs where their special skill and experience can be put to the best use for the needs of this country. The short table below gives details of the present position of the Basque children at present: — Occupation Girls Boys Domicile Girls Boys At School...... 41 45 Private homes 34 28 Continue studies Married ...... 10 2 with help of Billets ...... 61 171 Juan Vives Trust 25 28 With Foster Parents Employed...... 55 151 or Guardians ... 10 8 Members of British In Convents 8 3 Services...... 2 16 At University — 1 In care of Foster At Boarding School 3 3 Parents or In Hostels— Guardians 10 8 Caerleon 2 4 In Convents 8 J Carshalton 8 16 Married ...... 10 2 Finchley 6 8 Sick (in hospital) 3 1 Others ...... 9 9 Training in Hospital (sick) ... 3 1 Hospital 3 — Hospital (training) 3 — 157 254 157 254 Repatriation is still suspended and the 411 children have been refugees in this country for seven years—a much longer time than was envisaged. Many of the children are widely distributed over Great Britain, but a special effort is made to keep them in touch with one another. Many of the older girls are doing work of national importance and others are training as dressmakers and hairdressers, and, 292/946/35/82(iv)